2014
DOI: 10.12944/cwe.9.2.11
|View full text |Cite
|
Sign up to set email alerts
|

Potential Bacterial Consortium to Increase the Effectiveness of Beer Wastewater Treatment

Abstract: The main objective of this research is to determine the effectiveness of microbial consortia in beer wastewater treatment. The research was initiated with the isolation of soil microbial consortium that has been contaminated by beer waste water, followed by the selection of the best potential microbial beer wastewater treatment. At the end, the selection of the best microbial consortium was tested in beer wastewater treatment based on pollutant parameters namely biochemical oxygen demand (BOD), chemical oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
1
3
0
1
Order By: Relevance
“…Similarly, Paramita et al [ 19 ] have stated that degradation of proteins and organic nitrogen into ammonium (NH 4 ) raises the pH and becomes alkaline. The same finding by Anggraeni et al [ 20 ] also showed that consortium of Cronobacter sp. strain, Pseudomonas fluorescens , and Aeromonas sp.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Similarly, Paramita et al [ 19 ] have stated that degradation of proteins and organic nitrogen into ammonium (NH 4 ) raises the pH and becomes alkaline. The same finding by Anggraeni et al [ 20 ] also showed that consortium of Cronobacter sp. strain, Pseudomonas fluorescens , and Aeromonas sp.…”
Section: Resultssupporting
confidence: 79%
“…Microbes that are able to adapt more quickly can efficiently break down organic materials contained in the waste [ 25 ]. Pseudomonas is a common bacterium capable of degrading pollutants [ 20 ] although not so efficient in the current study compared to other isolates. High COD reduction in the treatment of brewery effluent by Pseudomonas species has also been reported [ 26 ].…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Dolayısıyla bira üretiminde ciddi miktarlarda arıtılması gereken atık su ortaya çıkmaktadır. Bira atık suyu, üretim sürecine ve işlem sırasındaki tüketim miktarına bağlı olarak organik madde içeren, biyolojik olarak parçalanabilen ve genellikle kayda değer miktarda ağır metal içermeyen özelliktedir [55], [57].…”
Section: Bira Atık Suyu (Beer Wastewater)unclassified
“…strain NGS4, Pseudomonas fluorescent NGS5, and Aeromonas sp. strain NGS7) with optimal oxygen flow (aeration), retention time and temperature showed reduction of COD by 67%, BOD by 79% and TSS by 50% [12]. The factors that affect the microbial ecology and characteristics of anaerobic reactors include Organic Loading Rate (OLR), Hydraulic Retention Time (HRT) and up low velocity [13].…”
Section: Introductionmentioning
confidence: 99%